Математичні моделі електротехнічних пристроїв як елементів систем - Чабан, В. Й. (Видавництво Національного університету «Львівська політехніка», 2007)
In the article the comparative analysis of basic types of mathematical models of electrical engineering devices is carried out under the corner of their use as models of elements of the electromechanics and autonomous electroenergy systems.